Revisit gut microbiota and its impact on human health and disease - Ding, Rui-xue; Goh, Wei-Rui; Wu, Ri-na; Yue, Xi-qing; Luo, Xue; Khine, Wei Wei Thwe; Wu, Jun-rui; Lee, Yuan-Kun (Yàowu shi͡p︡in fenxi, 2019)
Trillions of microbes have evolved with and continue to live on human beings. With the rapid advances in tools and technology in recent years, new knowledge and insight in cross-talk between the microbes and their hosts have gained. It is the aim of this work to critically review and summarize recent literature reports on the role of microbiota and mechanisms involved in the progress and development of major human diseases, which include obesity, hypertension, cardiovascular disease, diabetes, cancer, Inflammatory Bowel Disease (IBD), gout, depression and arthritis, as well as infant health and longevity. [Display omitted] •Gut microbiome plays major roles in maintenance of human health.•Gut microbiome is involved in progress and development of human diseases.•These include metabolic and inflammatory disorders, cancer, depression, as well as infant health and longevity.•Rapid advancements in technology has provided new insights regarding mechanisms behind host-microbiome interactions.